Studi Eksploratif tentang Efektivitas Manajemen Stres Berbasis Mobile Health Application pada Tenaga Kesehatan - Shofwatun Amaliyah; Dody Indra Sumantiawan (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Healthcare professionals often face high levels of stress due to demanding job requirements, which can negatively impact their mental and physical health. Mobile health applications have emerged as potential tools to assist in stress management. This study aims to evaluate the effectiveness of mobile health applications in reducing stress among healthcare professionals. The study utilizes a literature review method by identifying, selecting, and analyzing 12 relevant research articles. The article search was conducted across several databases such as Science Direct, PubMed, Springer, Elsevier, and Google Scholar. Inclusion criteria encompass articles that discuss the use of mobile health applications for stress management among healthcare professionals, published within the last 10 years. Data were thematically analyzed to identify key findings related to the effectiveness of these applications. The literature review results indicate that mobile health applications are effective in reducing stress levels and improving the psychological well-being of healthcare professionals. Successful implementation requires attention to factors influencing adoption and usage, as well as strategies to overcome existing barriers. Further research is needed to evaluate the long-term effects and develop practical recommendations to enhance the effectiveness of these applications.